Chapter 1 Animal sacrifice, politics and the law in Tamil Nadu, South India - Good, Anthony (Taylor & Francis, 2023)
After describing and explaining the significance of animal sacrifice in a typical Tamil village goddess festival, this chapter considers the debates surrounding the passing of the Madras Animals and Birds Sacrifices Prohibition Act 1950 and addresses the puzzling issue of its non-enforcement. Why did Chief Minister Jayalalitha suddenly insist upon implementing the Act more than 50 years later, and why did she so quickly change her mind? These legislative and policy reversals are set against a background of tensions between the competing visions of religiosity held by reformist, urbanised, generally high-caste Hindus and their traditionally minded, rural, generally lower-caste counterparts. When ruling on such issues the higher Indian courts display strong reformist tendencies, further reinforced in recent years by the growing influence of the extreme brand of reformism known generically as Hindutva. The political and legal dimensions of these struggles have emerged even more clearly in the more recent jallikattu (bull-taming) controversy.